2018
DOI: 10.1016/j.bbadis.2017.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Repopulating the biliary tree from the peribiliary glands

Abstract: The larger ducts of the biliary tree contain numerous tubulo-alveolar adnexal glands that are lined with biliary epithelial cells and connected to the bile duct lumen via small glandular canals. Although these peribiliary glands (PBG) were already described in the 19th century, their exact function and role in the pathophysiology and development of cholangiopathies have not become evident until recently. While secretion of serous and mucinous components into the bile was long considered as the main function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 70 publications
2
43
0
Order By: Relevance
“…(15) However, over the past decade, PBG cells have been characterized in more detail and stem cell properties of PBG have come to light. (1,3,16,17) Although marked proliferation of PBG in the context of large bile duct pathologies has been described for hepatolithiasis, for primary sclerosing cholangitis, and after ischemia, (4)(5)(6) today's view on PBG and their counterparts in the pancreas and liver suggests that several other hepato-pancreato-biliary diseases are also linked with these progenitor cell compartments. (2,18,19) In support of this, the current ex vivo study demonstrated the central role of PBG in bile duct recovery after severe ischemic damage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(15) However, over the past decade, PBG cells have been characterized in more detail and stem cell properties of PBG have come to light. (1,3,16,17) Although marked proliferation of PBG in the context of large bile duct pathologies has been described for hepatolithiasis, for primary sclerosing cholangitis, and after ischemia, (4)(5)(6) today's view on PBG and their counterparts in the pancreas and liver suggests that several other hepato-pancreato-biliary diseases are also linked with these progenitor cell compartments. (2,18,19) In support of this, the current ex vivo study demonstrated the central role of PBG in bile duct recovery after severe ischemic damage.…”
Section: Discussionmentioning
confidence: 99%
“…PBG have been shown to contain cell types with pluripotent properties, typical of stem/progenitor cells . Recent advances have unraveled the phenotypical heterogeneity of PBG along the extrahepatic and large intrahepatic bile ducts, and PBG have been proposed as a key element in the pathophysiology of liver, pancreas, and bile duct . In this concept, PBG are activated upon injury and driven by molecular pathways to restore the compromised integrity of the luminal biliary epithelium in various cholangiopathies.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, such bile duct injuries may be repaired by EHBD progenitors in peribiliary glands (PBGs), so-called pseudopyloric glands (PPGs) in pathology (Cardinale et al, 2012;Carpino et al, 2012;DiPaola et al, 2013), which are alveolar-like glands composed of serous and mucinous acini (Hopwood et al, 1988;Sugiura and Nakanuma, 1989;Zimmermann, 2016). In both humans and mice in the normal healthy state, few glandular structures exist in the gallbladder, but SOX9-positive PBGs are distributed widely throughout the ductular walls of cystic ducts and other proximal parts of the biliary tract, indicating a possible role in the physiological maintenance of the barrier function of bile duct epithelia (Furuyama et al, 2011;de Jong et al, 2018). However, the SOX17/SOX9 expression profiles and PBG/PPG dynamics in human BA infants, despite having a well-preserved gallbladder in some of the 'isolated' BA cases, remain to be characterized.…”
Section: Introductionmentioning
confidence: 99%